Aristocracy, politics and power in Byzantium, 1025-1081 - Nilsson, J (2017)
The purpose of this thesis is to further our understanding of the period between the death of Basil II in 1025 and the accession of Alexios I Komnenos in 1081. Modern scholarship has often portrayed these 56 years as an important, transformative period, viewing the empire as standing at the height of its power at its beginning, only to be brought to the brink of collapse by civil wars and foreign invasions following the battle of Manzikert in 1071. Based on three unique and underexploited sources of evidence, namely the letters of Michael Psellos, the judicial handbook commonly known as the Peira and the so-called Consilia et Narrationes of Kekaumenos, it argues that the Byzantine state to a large extent relied on private networks to carry out public administration throughout the empire. Public and private power were thus intimately intertwined and by conveying information, orders and requests, but also by reproducing and enforcing norms of acceptable political behaviour, these networks served to compensate to some extent for the institutional shortcomings of the premodern state. It also challenges the idea that the political dynamic of the eleventh century was centred around the power struggles of ‘great families’ or clans that effectively functioned as political parties, as well as the idea that the emperors and their officials were apathetic about governing the provinces beyond what was necessary to pacify and extract resources from them. Taken together, the evidence examined consequently appears to suggest that, by the standards of the pre-modern world, the Byzantine empire had a reasonably well-functioning state and a fairly coherent society during the period in question, suggesting that the focus of the scholarly debate on the eleventh-century Byzantine collapse should, to some extent, be shifted from internal to external factors.